2007
DOI: 10.1128/mcb.00602-07
|View full text |Cite
|
Sign up to set email alerts
|

Linear Distance from the Locus Control Region Determines ε-Globin Transcriptional Activity

Abstract: Enhancer elements modulate promoter activity over vast chromosomal distances, and mechanisms that ensure restrictive interactions between promoters and enhancers are critical for proper control of gene expression. The human ␤-globin locus control region (LCR) activates expression of five genes in erythroid cells, including the proximal embryonic -and the distal adult ␤-globin genes. To test for possible distance sensitivity of the genes to the LCR, we extended the distance between the LCR and genes by 2.3 kbp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
(60 reference statements)
1
13
1
Order By: Relevance
“…In this sense, 5ЈHS1 may serve as a local enhancer that preferentially stimulates ⑀-globin, rather than functioning as a part of an LCR holocomplex. We have previously reported that ⑀-globin gene expression in primitive erythroid cells of YAC TgM is sensitive to distance from the LCR enhancer (24). Now, we showed here that efficient ⑀-globin gene transcription is critically dependent on 5ЈHS1 enhancer activity.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In this sense, 5ЈHS1 may serve as a local enhancer that preferentially stimulates ⑀-globin, rather than functioning as a part of an LCR holocomplex. We have previously reported that ⑀-globin gene expression in primitive erythroid cells of YAC TgM is sensitive to distance from the LCR enhancer (24). Now, we showed here that efficient ⑀-globin gene transcription is critically dependent on 5ЈHS1 enhancer activity.…”
Section: Discussionsupporting
confidence: 49%
“…The 5ЈHS1 (formerly termed HS1-3Ј) fragment was excised as a KpnI-XbaI fragment from the pHS1-3Ј/⑀-luc (24) and subcloned into KpnI/NheI-digested p␤-luc and pGV-P2 (TOYO INK) to generate p5ЈHS1/␤-luc and p5ЈHS1/GV-P2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we inserted a bacteriophage DNA (HindIIIdigested 2.3-kb) fragment into a human ␤-globin YAC at a position 3= to the locus control region (LCR) and generated YAC-TgM (32). As shown in Fig.…”
Section: Generation Of Yac-tgm Bearing Chimeric H19 Icr Sequencesmentioning
confidence: 99%
“…Together with the effects at the globin locus, these data suggest that the presence of KLF1 is critical for transcription initiation in facilitating the formation of an open chromatin configuration at target loci. These data raise the possibility that in addition to transcription initiation, KLF1 also plays a role in regulating transcription elongation in erythroid cells (67), since the interaction between the upstream LCR and the proximal ␤-globin promoter, whose 3D chromatin structure requires KLF1 (56,58), aids in establishing a postinitiation transcription elongation complex (68,69). KLF1 is also recruited to the ␣-globin promoter and one of its upstream enhancer elements at late stages of differentiation (60,70), possibly aiding in intrachromosomal interactions, preinitiation complex recruitment, and the transition from a poised to an elongating transcriptional state (70).…”
mentioning
confidence: 99%